Symmetry-Dependent Dielectric Screening of Optical Phonons in Monolayer Graphene - Loïc Moczko; Sven Reichardt; Aditya Singh; Xin Zhang; Elise Jouaiti; Luis E. Parra López; Joanna L. P. Wolff; Aditi Raman Moghe; Etienne Lorchat; Rajendra Singh; Kenji Watanabe; Takashi Taniguchi; et al. (Physical Review X)
Quantized lattice vibrations (i.e., phonons) in solids are robust and unambiguous fingerprints of crystal structures and of their symmetry properties. In metals and semimetals, strong electron-phonon coupling may lead to so-called Kohn anomalies in the phonon dispersion, providing an image of the Fermi surface in a nonelectronic observable. Kohn anomalies become prominent in low-dimensional systems, in particular, in graphene, where they appear as sharp kinks in the in-plane optical phonon branches. However, in spite of intense research efforts on electron-phonon coupling in graphene and related van der Waals heterostructures, little is known regarding the links between the symmetry properties of optical phonons at and near Kohn anomalies and their sensitivity towards the local environment. Here, using inelastic light scattering (Raman) spectroscopy, we investigate a set of custom-designed graphene-based van der Waals heterostructures, wherein dielectric screening is finely controlled at the atomic-layer level. We demonstrate experimentally and explain theoretically that, depending exclusively on their symmetry properties, the two main Raman lines of graphene react differently to the surrounding environment. While the 2D line, which is due to near-zone-edge optical phonons, undergoes changes due to the neighboring dielectric environment, the in-plane, zone-center optical phonons are symmetry protected from the influence of the latter. These results shed new light on the unique electron-phonon coupling properties in graphene and related systems and provide invaluable guidelines to characterize dielectric screening in van der Waals heterostructures and moiré superlattices.